Advances in microbial food safety - Sofos, J. (Elsevier Science : Woodhead Publishing, 2013)
New research, outbreaks of foodborne disease and changes to legislation mean that food microbiology research is constantly evolving. Advances in microbial food safety: Volume 1 summarises the key trends in this area for the food industry. The book begins with an introductory chapter discussing food safety management systems from the past to the present day and looking to future directions. The book moves on to provide updates on specific pathogens including Salmonella, Listeria monocytogenes and Bacillus species. New developments in the area are explored with chapters on emerging paras.
9 Advances in separation and concentration of microorganisms from food samples.
Keywords: Food -- Microbiology.; Food -- Safety measures.; Food -- Toxicology.; elektronické knihy; electronic books